1999
DOI: 10.1088/0967-3334/20/4/201
|View full text |Cite
|
Sign up to set email alerts
|

The electric resistivity of human tissues (100 Hz-10 MHz): a meta-analysis of review studies

Abstract: The electric resistivity of various human tissues has been reported in many studies, but on comparison large differences appear between these studies. The aim of this study was to investigate systematically the resistivities of human tissues as published in review studies (100 Hz-10 MHz). A data set of 103 resistivities for 21 different human tissues was compiled from six review studies. For each kind of tissue the mean and its 95% confidence interval were calculated. Moreover, an analysis of covariance showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
204
2
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(219 citation statements)
references
References 29 publications
6
204
2
7
Order By: Relevance
“…The four-electrode technique, coupled with distant placement of the current electrodes and high-impedance input circuitry, reduces the contribution of the skin and the subcutaneous fat to a negligible level (Shiffman et al, 1999). Moreover, of all tissues in a limb, muscle contributes by far the greatest extent to the EIM data since is has a very low resistivity (Faes et al, 1999) and relativity large volume, thus serving as the preferential path for electrical current flow.…”
Section: Discussionmentioning
confidence: 99%
“…The four-electrode technique, coupled with distant placement of the current electrodes and high-impedance input circuitry, reduces the contribution of the skin and the subcutaneous fat to a negligible level (Shiffman et al, 1999). Moreover, of all tissues in a limb, muscle contributes by far the greatest extent to the EIM data since is has a very low resistivity (Faes et al, 1999) and relativity large volume, thus serving as the preferential path for electrical current flow.…”
Section: Discussionmentioning
confidence: 99%
“…The leg-to-leg bioimpedance is a rapid and noninvasive method to assess body composition (Nunez et al, 1997) and this is the first study to compare this method in different ethnic groups living within their native countries. The larger increase in impedance index per unit increase of BMI -showed by the different slopes and interceptsobserved in West African and Asian Indian women compared with white Caucasian women may arise from an increased bone mineral content and/or adiposity -both of which are less hydrated and thus have higher resistance (Faes et al, 1999). This speculation is supported by previous studies which have shown an increased body mineral content in African populations (Barondess et al, 1997;Wagner and Heyward, 2000) and a higher adipose tissue in Asian Indians compared to white Caucasians (Bose, 1995;Orr-Walker et al, 2005;Bhansali et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The human body can be divided into different components (fat, mineral, protein and water) which have specific physical properties and show a characteristic response to the application of a small, electrical current, as used in bioimpedance analysis (BIA) (Faes et al, 1999;Ellis, 2000). BIA has emerged as one of the most widely used methods to assess body composition because it is quick, can be undertaken in the field and is relatively inexpensive.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency range was decided by referring to the previous studies that are relevant to the electrode polarization in low frequencies. [19][20][21][22][23] An operating voltage of 100 mV rms was applied to the electrodes considering the induced voltage that can cause damage to the bio-tissues. 24 The needle and the sample had a floating potential with respect to the electrodes.…”
Section: Methodsmentioning
confidence: 99%